Novel case of recurrent intraventricular atypical central neurocytoma with prominent gangliogliomatous differentiation in a 10‐year‐old boy with 10 years of follow up. Issue 5 (24th July 2018) - Tan, Char‐Loo; Landi, Daniel; Fuchs, Herbert; McLendon, Roger E.
Abstract : Central neurocytoma is a rare neuronal tumor that typically occurs in young adults. Infrequently, these tumors exhibit advanced neuronal maturation and glial differentiation, giving rise to a histologically diverse tumor, in contrast to a typical central neurocytoma. We present a novel case of intraventricular central neurocytoma with prominent gangliogliomatous differentiation that developed atypical features upon recurrence after 10 years of follow up in a 10‐year‐old boy. Our case provides insight into the divergent differentiation capability of a neurocytic tumor and illustrates the diverse histological features of this rare entity.